ANALISIS VARIABEL YANG BERHUBUNGAN DENGAN PERILAKU KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA PROYEK TOL DALAM KOTA JAKARTA UTARA TAHUN 2021 - Evelyn Octa Triana (2021)
In Indonesia, the proportion of work accidents in the construction sector reaches 32%, this number can be reduced by reducing various unsafe actions. There is an increase in the intensity of the Section 1A KSO Jaya Kontruksi-Adhi Inner City Toll project, workers only focus on work targets and forget the importance of working safely and safely, namely using PPE. The purpose of this study was to analyze variables related to compliance behavior using Personal Protective Equipment (PPE) in North Jakarta City Toll Project Workers Section 1A KSO Jaya Kontruksi-Adhi. This research is a quantitative analytic study using bivariate analysis. The population is 150 workers and the sample is 120 workers with accidental sampling technique. This research instrument in the form of questionnaires and observation sheets. The results of the bivariate test analysis showed a significant relationship between the variables of knowledge (p = 0.047), attitude (p = 0.003) and the availability of PPE (p = 0.001) on the use of PPE by workers. Suggestions for companies to provide more PPE that is sufficient and equal in number to the number of workers. Workers are expected to be obedient in using PPE because to create a safe and comfortable atmosphere at work.